Executive Control Deficits Potentiate the Effect of Maladaptive Metacognitive Beliefs on Posttraumatic Stress Symptoms - Bardeen, Joseph R.; Fergus, Thomas A. (Frontiers in Psychology, 2018)
The metacognitive model and recent preliminary research suggests that metacognitive beliefs (i.e., beliefs about thinking) may be particularly important for understanding the pathogenesis of posttraumatic stress (PTS). The metacognitive model also suggests that deficits in executive control (i.e., metacognitive control) may increase the impact of metacognitive beliefs on PTS symptoms. Trauma-exposed adult participants (N = 469), recruited through an online crowdsourcing website, completed a battery of measures assessing the constructs of interest. As predicted, deficits in executive control strengthened the positive association between metacognitive beliefs and PTS symptoms. This effect was found in relation to positive (e.g., “Worrying will keep me safe”), but not negative (e.g., “My thoughts are uncontrollable”), metacognitive beliefs. Supplemental analyses, indicated that the interaction between positive metacognitive beliefs and executive control significantly predicted all PTS cluster scores (i.e., Intrusion, Cognition, Arousal, Avoidance). Taken together, results support the proposal that executive control deficits potentiate the effect of metacognitive beliefs on PTS symptoms. Intervention strategies designed to strengthen executive control (e.g., the attention training technique) may be useful in treating individuals with PTS.